Transformational Leadership and Trust on Organizational Commitment at State Senior High School - Kusmayadi Kurniawan; Bedjo Sujanto; Rugaiyah Rugaiyah (Faculty of Economics, State University of Jakarta., 2019)
The purpose of this research is to know the effect of transformational leadership and trust toward organizational commitment teachers at state high school in the city of depok. The research was conducted using survey method with quantitative approach and path analysis technique. The population of this research is 256 teachers. Research samples selected as much as 156 teacher using simple random sampling technique. The data obtained through questionnaires and analyzed using path analysis techniques. Based on the result of data analysis in the research it is conclude: First, transformational leadership have positive direct to organizational commitment. Second, trust have positive direct to organizational commitment, and third, transformational leadership have positive direct to trust. Organizational commitment can be improve through improvement of transformational leadership and trust.